Thyroid isthmus agenesis coinciding with papillary thyroid carcinoma: a case report - Hamiedah, Murad M.; Al-Bdour, Bilal; Alshoubaki, Wael I.; Al-Nawaiseh, Hussien R.; Aljaafreh, Hamza M. (International Journal of Advances in Medicine, 2024)
Thyroid isthmus agenesis is a rare congenital anomaly characterized by the absence of the thyroid isthmus. Papillary thyroid carcinoma (PTC) is the most common type of thyroid malignancy. The coexistence of thyroid isthmus agenesis and PTC is extremely rare, with limited cases reported in the literature. This case report aims to describe a rare presentation of thyroid isthmus agenesis coinciding with PTC, detailing the clinical presentation, diagnostic approach, and management. Here, we discuss a case of a 49-year-old female presented with neck pain attributed to a cervical disc issue. An MRI scan incidentally identified a left thyroid lesion measuring 5×2.5 cm. Neck ultrasound confirmed a 2.4×2.7×4.2 cm lesion in the left lobe with no suspicious lymph node enlargement. Fine-needle aspiration (FNA) biopsy indicated PTC, classified as Bethesda VI. The patient underwent total thyroidectomy. Intraoperatively, the absence of the thyroid isthmus was noted. Histopathology confirmed a unifocal, 3.9×1.8 cm PTC of the classic subtype, staged as PT2pNx, with no neurovascular invasion and a tumor-free left thyroid lobe. The patient had an uneventful recovery and was discharged two days postoperatively. The absence of the thyroid isthmus can complicate surgical procedures. Preoperative imaging and careful intraoperative management are crucial. This case report highlights the rarity of thyroid isthmus agenesis coinciding with PTC, and emphasizes the importance of recognizing anatomical variations and their implications for surgical management and prognosis. Although it is hypothesized that abnormal development may predispose to malignancy, further studies are warranted to explore the potential association between congenital thyroid anomalies and thyroid malignancy.